Synanthropization of riparian plant communities in the Ojców National Park (Southern Poland) - Sołtys-Lelek, Anna; Barabasz-Krasny, Beata; Możdżeń, Katarzyna (Biodiversity: Research and Conservation, 2016)
Although riparian forests are still common in Europe, their variants - similar to natural forests - are rare. They are, as communities, early stages of forest-shrub succession, particularly vulnerable to the expansion of neophytes for which they are an important type of vegetation that enables their spread. In the Ojców National Park (ON P), these types of phytocoenoses are heavily influenced by anthropogenic pressure. The preservation of their biodiversity is particularly difficult because of the fragmentation and small area occupied by the Park - just 2.89 ha. There have been no data on synanthropization of ON P riparian forests until now. The ‘conservation status’ of these communities was determined by examining the degree of anthropophyte participation in their floristic composition. This determination is necessary to take effective preventive measures. In 2012-2014, phytosociological studies were carried out on the ON P riparian communities. A particular attention was paid to the presence and quantitative participation of alien species in research plots. The obtained results revealed that there were 189 plant species in alluvial forests of the ON P, including 80 synanthropic species. The group of synanthropes comprised 32 anthropophytes: 5 diaphytes, 9 archaeophytes and 18 kenophytes.